Something true : a true love novel - Scott, Kieran, 1974- (Scott, Kieran, 1974- True love novel, 2015)
Eros, the Goddess of Love, in her guise as True, a modern-day New Jersey high school student, tries to match a third couple, the last one required for her to be reunited with her own true love, Orion, and return to Olympus.